ANALSISIS PENERAPAN MODEL CIPP TERHADAP PENYEDIAAN LAYANAN PENDIDIKAN INKLUSI DI TAMAN KANAK-KANAK PERTIWI DI KECAMATAN BUKIK BARISAN - Yulianti, Khairu Nisa; Khairiah, Fisna; Yaswinda (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2023)
The study was intended to identify the catchment of the Ministry of Education for the Early Childhood Education Society according to the Ministry of Education and Culture number 18, 2018 By using the CIPP analysis model (context advance, input, process, and product) the object in the study is in the nub district of the fifty city district with the number of children of 18 normal children and 3 children infiltrating by 2 faculty and 1 escort teacher. The study was carried out Thursday to Friday, March 15 to 16, 2023. The study uses qualitative descriptive methods and uses CIPP model analysis. His data-collection techniques include observation interviews and documentation. Studies show that children in kindergarten have been provided several tools and infrastructure to support successful child study such as teaching materials and assessments that have been adjusted to the needs of children, but this has not been fully realized since there has been no specific inclusion teacher that teachers at the school give priority to normal children.